Effects of buprenorphine on nociception and spontaneous locomotor activity in horses - Carregaro, Adriano B.; Luna, Stélio Pacca Loureiro [UNESP]; Mataqueiro, Maria Isabel; de Queiroz-Neto, Antonio (Amer Veterinary Medical Assoc, 2007)
Objective-To investigate spontaneous locomotor activity (SLA) and antinociceptive effects of buprenorphine in horses.Animals-6 healthy adult horses.Procedures-Horses received each of 3 treatments (10 mL of saline [0.9% NaCl] solution, 5 mu g of buprenorphine/kg, or 10 mu g of buprenorphine/kg). Treatments were administered IV Order of treatments was randomized, and there was a 10-day interval between subsequent treatments. Spontaneous locomotor activity was investigated in a behavioral box by use of infrared photoelectric sensors connected to a computer, which detected movement of each horse. Antinociceptive effect was investigated by hoof-withdrawal reflex latency (HWRL) and skin-twitching reflex latency (STBL) after painful stimulation with a heat lamp.Results-Moderate excitement was observed in all horses from 5 to 10 minutes after the administration of both dosages of buprenorphine. The SLA increased significantly for 6 and 14 hours after IV administration of 5 and 10 mu g of buprenorphine/kg, respectively. Values for HWRL increased significantly only at 30 minutes after injection of 5 mu g of buprenorphine/kg, whereas STRL and HWRL each increased significantly from 1 to 6 hours (except at 2 and 4 hours) and 11 hours, respectively, after injection of 10 mu g of buprenorphine/kg.Conclusions and Clinical Relevance-IV injection of buprenorphine caused a dose-dependent increase in SLA, but only the dose of 10 mu g/kg induced analgesia on the basis of results for the experimental method used.